On reciprocal behavior in prisoner dilemma game - Ahmed Doghmi; Miloudi Kobihy (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
In this paper, we introduce the concept of payoff distortion in the standard prisoner's dilemma game when strategies are driven by psychological behaviors. This concept enables to take account each player's assessment of the other player's behavior and the asymmetry of information. We determine the conditions which allow that mutual cooperation constitutes the equilibrium. we particularly focus on the reciprocity in case of complete and incomplete information about the payoff distortion. We show that mutual cooperation is a Nash equilibrium with complete information and is a Bayesian equilibrium when each player believes that his opponent behaves with 'large' reciprocity in incomplete information environment.
Keywords: C7; A13; 330; Reciprocity; Behavior; Cooperation; prisoner's dilemma game; Gefangenendilemma; Austauschtheorie; Spieltheorie; Theorie